Occupational Heat Exposure With Related Symptoms And Its Contributing Factors Among Workers In The Automotive Industry - Intan Najmin Sabrina, Mohamed Haneef (2025)
Occupational heat exposure is a significant concern in industries with high physical demands in a hot and humid work environment, such as automotive manufacturing. This study investigates occupational heat exposure with related symptoms and its contributing factors among automotive workers, aiming to highlight the risks associated with various contributing factors. A cross-sectional study was conducted among automotive workers exposed to high heat levels due to tasks involving heavy machinery and enclosed work areas. Data were collected using structured questionnaires, environmental measurements, and observational analyses. Key contributing factors fall under engineering and administrative characteristics, medical and working conditions, and personal characteristics. The findings reveal that the selected workstations exceeded the Threshold Limit Value of workstations temperature indicating high risk. Reported half of the heat-related symptoms, including dry mouth, dizziness, severe thirst, heat rash, inability to concentrate, hot dry skin, and headache were prevalent among workers. Contributing factors included the substitution of work (mechanization), the presence of acclimatization, hazard identification, workspace adequacy, and a lack of heat prevention awareness. Workers engaged in physically demanding tasks or those in areas with poor air circulation were at higher risk of experiencing heat-related illnesses. There was a significance relationship between the level of occupational heat exposure and its contributing factors towards heat-related symptoms among workers in the automotive industry. It underscores the urgent need for effective heat stress management strategies, such as engineering controls to reduce workplace temperatures, administrative measures to ensure adequate breaks and hydration, and educational programs to enhance workers' understanding of heat-related risks. Addressing these factors can significantly reduce heat-related symptoms and improve occupational health and safety in the automotive sector.